2023
DOI: 10.3389/fimmu.2023.1125190
|View full text |Cite
|
Sign up to set email alerts
|

Hemagglutinin expressed by yeast reshapes immune microenvironment and gut microbiota to trigger diverse anti-infection response in infected birds

Abstract: IntroductionThe H5N8 influenza virus is a highly pathogenic pathogen for poultry and human. Vaccination is the most effective method to control the spread of the virus right now. The traditional inactivated vaccine, though well developed and used widely, is laborious during application and more interests are stimulated in developing alternative approaches.MethodsIn this study, we developed three hemagglutinin (HA) gene-based yeast vaccine. In order to explore the protective efficacy of the vaccines, the gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The symbiotic microbiota, which consists of trillions of microorganisms, plays a crucial role in regulating various host physiological functions, such as digestion, nutrient metabolism, and immune system development [ 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 ]. Recently, mounting evidence has suggested that the gut microbiota modulates the host’s susceptibility to viral infections and contributes to various immune protective mechanisms against influenza virus infection [ 18 , 19 , 20 , 88 , 139 , 140 , 141 , 142 , 143 , 144 , 145 ]. Neomycin-sensitive bacterial communities continuously provide signals for the transcription of Il1b and Il18 , contributing to pulmonary protective immune responses during influenza virus infection [ 18 , 139 ].…”
Section: The Role Of Commensal Microbiota In Influenza Virus Infectionmentioning
confidence: 99%
“…The symbiotic microbiota, which consists of trillions of microorganisms, plays a crucial role in regulating various host physiological functions, such as digestion, nutrient metabolism, and immune system development [ 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 ]. Recently, mounting evidence has suggested that the gut microbiota modulates the host’s susceptibility to viral infections and contributes to various immune protective mechanisms against influenza virus infection [ 18 , 19 , 20 , 88 , 139 , 140 , 141 , 142 , 143 , 144 , 145 ]. Neomycin-sensitive bacterial communities continuously provide signals for the transcription of Il1b and Il18 , contributing to pulmonary protective immune responses during influenza virus infection [ 18 , 139 ].…”
Section: The Role Of Commensal Microbiota In Influenza Virus Infectionmentioning
confidence: 99%